2015
DOI: 10.1002/pen.24123
|View full text |Cite
|
Sign up to set email alerts
|

An exfoliated clay-poly(norbornene) nanocomposite prepared by metal-mediated surface-initiated polymerization

Abstract: An exfoliated clay−polymer nanocomposite was prepared by surface‐initiated ring opening metathesis polymerization (SI‐ROMP) of norbornene on a montmorillonite (MMT) clay with a modified surface. Utilizing the hydrothermal‐silylation reaction between a norbornenyl‐bearing chlorosilane agent and silanol groups of the MMT clay, we were able to bind a metal alkylidene catalyst to the surface in order to grow poly(norbornene) chains directly from the surface using ROMP. Our approach produced nanocomposites having p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 40 publications
0
11
1
Order By: Relevance
“…The first sample is a physical mixture of the clay template and the polymer where a phase separation was observed. This was completely different from the TEM micrograph of the nanocomposite where the silicate clay platelets can be [Penaloza et al, 2015] observed homogeneously dispersed within the boundaries of the polymer matrix ( Figure 8B). This confirms that the polymer chains are covalently attached to the clay.…”
Section: Introductioncontrasting
confidence: 69%
See 4 more Smart Citations
“…The first sample is a physical mixture of the clay template and the polymer where a phase separation was observed. This was completely different from the TEM micrograph of the nanocomposite where the silicate clay platelets can be [Penaloza et al, 2015] observed homogeneously dispersed within the boundaries of the polymer matrix ( Figure 8B). This confirms that the polymer chains are covalently attached to the clay.…”
Section: Introductioncontrasting
confidence: 69%
“…The procedure described below has been published elsewhere (Penaloza, Seery, 2011;Seery & Penaloza, 2013;Penaloza et al, 2015). A 100 mg C15Asil was placed in 20-mL scintillation vial and was brought inside glovebox.…”
Section: Synthesis Of Clay-poly(norbornene) Nanocompositesmentioning
confidence: 99%
See 3 more Smart Citations